Recurrent de novo MAPK8IP3 variants cause neurological phenotypes. Issue 6 (25th April 2019) - Iwasawa, Shinya; Yanagi, Kumiko; Kikuchi, Atsuo; Kobayashi, Yasuko; Haginoya, Kazuhiro; Matsumoto, Hiroshi; Kurosawa, Kenji; Ochiai, Masayuki; Sakai, Yasunari; Fujita, Atsushi; Miyake, Noriko; Niihori, Tetsuya; et al.
Abstract : c‐Jun‐amino‐terminal kinase‐interacting protein 3 (JIP3), encoded by MAPK8IP3, is an adaptor protein of the kinesin‐1 complex and essential for axonal transport in neurons. However, an association between MAPK8IP3 variants and human disease has not been established. We identified 5 individuals from four families with recurrent de novo variants c.1732C>T (p.Arg578Cys) and c.3436C>T (p.Arg1146Cys) in MAPK8IP3 . The core phenotype includes spastic diplegia, intellectual disability, cerebral atrophy, and corpus callosum hypoplasia. Zebrafish embryos overexpressing human mutant JIP3 showed axon varicosities of the posterior lateral line nerve, suggesting an adverse effect on the developing axons. Our results suggest that MAPK8IP3 variants cause a neurodevelopmental disease. ANN NEUROL 2019;85:927–933.